Zero Tolerance = 100 New Techniques Swedish / Nordic Street Art - Calderon Alaez, Elena (Street Art & Urban Creativity, 2020)
Just as citizens design the city with their actions, with their walks, their routes (as the classic example of paths created in parks on the grass, the so-called "Desire Lines") the artists, in this case, focused on the the Nordic cities (specifically Stockholm) have designed or developed their new ways of acting on the city, using new techniques, materials and especially supports (which are not so common in the scene of independent public art in the cities of Southern Europe). It draws attention in how in cities of northern Europe, advertising has captured all possible public space supports. Even in transports like subway, trams ... etc or placing giant screens in crowded areas of the city center or completely papering the buildings and fences with thousands of posters. The intervention (Photo 1) of the Swedish street artist Klisterpeter, of 2011, does not represent the truth. It is an ironic intervention, since contrary to how it is expressed here, we could say that Stockholm "hates" graffiti. Probably the rest of European cities hate it in equal measure, although in this city, compared to others like Barcelona, Berlin, Athens or Lisbon, graffiti its totally absence. In this article we will try to find the reason for this fact, looking for a parallelism with the well-known Nordic design and through its different cultural uses. If you have heard about Ikea, you know exactly what we are going to talk about. The main idea that transmits is not to fill the space of pieces without use, which can be compared with the care of urban artists/ graffiti artists in the Swedish capital, the simplicity in the lines, the soft colours, the minimalism and the principle of "less is more" that is perfectly described in their daily life. The Scandinavian character united to the environment that surrounds them: the cold, the darkness and the great virgin forests, have been very influential factors.